Carbon fiber-reinforced polymers as a tensile reinforcement of the Pinus elliotti and Manilkara huberi wood species - dos Santos Bravo, Cintia Grazielle Alves; Nunes Branco, Luiz Antonio Melgaço; Chahud, Eduardo; de Moura Aquino, Vinicius Borges; Pereira Geraldes Dias, Alfredo Manuel; Christoforo, Andre Luis; Rocco Lahr, Francisco Antonio (Maderas. Ciencia y Tecnología, 2020)
In wood structures, the elements subjected to bending stresses, such as the beams, present a fracture initiated in the tensile region, and under these conditions, the use of laminated composite materials is presented as an alternative solution in the form of repair or reinforcement. This research aimed to evaluate the influence of the use of carbon fibers laminated composites in tensile reinforcement in the direction parallel to grain of Pinus elliotti and Manilkara huberi wood species. The Viapol two-component epoxy adhesive was used in the lamination and fixation of the unidirectional carbon fiber in the wood species. Ten specimens with no defects (reference) and 10 specimens were prepared for each crack length (25 and 50mm) with and without the reinforcement (60mm × 50mm) by the laminated composite. The tensile tests were performed in accordance with the requirements of the Brazilian standard ABNT NBR 7190 (1997). From the results of the statistical analysis, the use of the carbon fiber composite was able to restore the tensile strength of the cracked samples (partial or total) in relation to samples without defects, demonstrating the potential of the laminates in carbon fibers as an alternative solution in repair for both wood species.